Mainstreaming gender and youth in Ghanaian agriculture policy - Komi Marcus, Larry; Ockrah-Anyim, Irene; Ovulley, Edna (Technical Centre for Agricultural and Rural Cooperation, 2018)
To encourage policy-makers to more effectively mainstream gender and youth in agriculture in Ghana, Syecomp Ghana Ltd. developed a position paper that highlighted key entry points that could enable young Ghanaians to effectively engage in agricultural value chains. By organising two regional workshops to feed into the position paper, stakeholders were given space for constructive and open discussions on the constraints and opportunities for the entry of young people into the sector.